Afastamentos do trabalho na enfermagem de um hospital geral no período de 1995 a 1999 - Barboza, Denise Beretta (2001)
The nursing working conditions in hospitals have been considered insalubrious since these workers are liable to many risks including physical, chemical, biological, ergonomic, mechanical and psychosocial. As a result of this exposure, they may become ill; consequently staying off work. This is an epidemiological study with a census to describe the working absences due to sick leave of nurses from a general teaching hospital. These absences were registered at the Centro de Atendimento ao Trabalhador (CEAT) in the period from 1995 to 1999. A total of 1,002 registrations of absences from working of members of nursing team was analyzed: 9.1% nurses, 1.7% nursing technicians, 69.7% nursing assistances and 19.5% of nursing orderlies. These people were related to 1,986 episodes of sick leave during the studied period: 1,826 (91.4%) by health licenses; 123 (6.2%) by working accidents; and 37 (1.2%) by maternity leave. According to the analysis of characteristics related to these absentees, the majority was women and workers aged between 31 to 40 years old, married, with full-time work of 1 to 6 years; in general, the period of time spent away from work was 1 to 4 days, and mostly employees were working in complex units. The characteristics of the episodes of absenteeism by health licence were frequently due to genito-urinary problems, badly defined diseases and respiratory system diseases. The nursing assistants and the nursing orderlies had registration of all classifications of the International Statistical Classification of Disease and Related Health Problems (1994). This study showed some ethic-legal infractions mainly in relation to the nursing orderlies as well as showing several factors which may be related to the episodes of working absences. Therefore, it may give ways to better analysis of this situation in the hospital improving the current working conditions; moreover, a further deeper investigation of absenteeism which causing more serious and longer problems.